No evidence for an indirect benefit from female mate preference in Arctic charr Salvelinus alpinus, but female ornamentation decreases offspring viability - Janhunen, Matti; Kekäläinen, Jukka; Kortet, Raine; Hyvärinen, Pekka; Piironen, Jorma (Biological Journal of the Linnean Society, 2011)
v 2012 ok